Fonio returns to Senegal - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Senegal, like many other countries in Africa, has a high import bill for much of its food stuffs, with national production of cereals way below local demand. Relief may be hand in the form of fonio (Digitaria exilis), a graminate introduced in the...